Batas Usia Nikah Dalam Undang-Undang Nomor 16 Tahun 2019 Tentang Perkawinan Ditinjau Dengan Konsep Maslahah Mursalah Imam Asy-Syathibi - Gustang Gustang; Hartono Hartono; Achmad Fahruddin (CV. ITTC INDONESIA, 2025)
Law Number 16 of 2019 concerning Marriage changed the provisions of the minimum age for marriage in Indonesia. Previously, according to Law Number 1 of 1974 concerning Marriage, the minimum age for marriage for women was 16 years, while for men it was 19 years. After the amendment was passed on October 14, 2019, the minimum age for marriage for women and men is now the same, namely 19 years. The reasons for the revision are to protect children's rights, prevent early marriage, and ensure the welfare of women and children in marriage. Other reasons for the change are the high rate of child marriage in Indonesia, the high divorce rate of women who marry under the age of 18, and low levels of education. Imam Asy-Syathibi formulated five objectives for the revelation of Islamic law known as al-maqasid asy-syari`ah. The five al-maqasid asy-syari`ah are: Hifdzu al-Din (protecting religion), Hifdzu al-Nafs (protecting the soul), Hifdzu al-Aql (protecting the mind), Hifdzul al-Mal (protecting property), and Hifdzu al-Nasab (protecting descendants).